KETERSEDIAAN MEDIA PEMBELAJARAN EKONOMI KELAS X DI MADRASAH ALIYAH KHULAFAUR RASYIDIN SUNGAI RAYA - Victor Halim; Parijo Parijo; Khosmas Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractAn analysis of availability learning media in teaching learning process in 10th grade Economic class of MA Khulafaur Rasyidin Sungai Raya.” General issue in this script is “to describe the availability learning media in teaching learning process in 10th grade Economic class. The Sub issues are how the availability learning media with traditional basis and technology basis, what is the Economic teacher issues found in order to full fill the availability of learning media process, and how teacher effort to resolve the availability learning media in in teaching learning process in 10th grade Economic class of MA Khulafaur Rasyidin Sungai Raya. The instrument for collecting data in this script are interview guidance, note book and checklist paper. Analysis of this script presented in qualitative descriptive with the resource is Economic teacher of MA Khulafaur Rasyidin. The result of this research shows in order to full fill availability of learning media in MA Khulafaur Rasyidin is very low and just limited in learning media with traditional basis also very low in instruments and infrastructures for school party also other obstacles in order to full fill the availability of learning media. Keywords: Availability learning media,teaching learning process, economic class.